Pengembangan Model Layanan Bimbingan Kelompok dalam Menumbuhkan Sikap Empati untuk Mengurangi Perilaku Bullying di Kalangan Siswa SMA PGRI 4 Denpasar Tahun 2026 - Ni Putu Krisnayanti Putri; Roro Dwi Umi Badriyah; I Gusti Lanang Rai Arsana (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
This study aimed to develop a group guidance service model to foster students’ empathy in order to reduce bullying behavior among students at SMA PGRI 4 Denpasar and to determine the feasibility of the developed model. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects included material experts, guidebook experts, school counselors, and 12 tenth-grade students of SMA PGRI 4 Denpasar. Data were collected through observation, questionnaires, expert validation, pre-tests, and post-tests. The results showed that the developed group guidance service model obtained a content validity score of 1.00, indicating a very high level of validity. The trial results revealed an improvement in students’ empathy, with an average N-Gain score of 0.13, which falls into the low category. Students’ responses to the developed model reached 84.25%, indicating that the model was highly feasible. Therefore, the developed group guidance service model is considered valid and feasible for use in fostering students’ empathy and helping to reduce bullying behavior in the school environment.